EFFORT TO DEVELOP CHILDREN'S COGNITIVE ASPECT IN SHOWING EXPLORATORY AND PROBING ACTIVITIES USING EXPERIMENTAL METHOD AND MAKE A MATCH MODEL - Inderianty, Putri (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
This research aims to describe the implementation and to develop the cognitive aspects of children through activities that show exploratory and probing activities by using experimental design and make a match model. This research is classroom action research with subjects were children in group B RA Raudhatul Jannah Banjarmasin academic year of 2015/2016, 2nd semester. The results showed that experimental method and make a match model can develop children's cognitive abilities.